Friction stir welding of dissimilar metals: Investigating the role of interlayers in aluminium-steel butt joint performance - Gunjal, Y.R; Sahu, M.; Gadakh, V.S; Badheka, V.J; Luqman Hakim, Ahmad Shah; Khemnar, N.S; Shinde, V.B (Elsevier, 2026)
This study explores the improvement of the mechanical properties of friction stir-welded (FSW) butt joints between aluminium and steel in a butt configuration by incorporating nickel (Ni), zirconium (Zr), and titanium (Ti) interlayers based on the Miedema model↱. The joint without an interlayer exhibited a tensile strength of 100 ± 8 MPa. However, the introduction of interlayers significantly enhanced joint strength. The Ti interlayer exhibited the highest tensile strength, reaching 147 ± 15 MPa, which corresponds to a 49 % increase. The Zr interlayer followed, achieving 115 ± 8 MPa, a 17 % improvement, while the Ni interlayer reached 105 ± 12 MPa, a 7.5 % increase. The optimal conditions for the Ti-interlayered joint were determined to be a tool rotational speed of 765 rpm, weld speed of 50 mm/min, and tool tilt of 1◦. Microstructural analysis revealed that the superior performance of the Ti interlayer was due to the formation of a ductile AlFeTi₂ phase and a refined microstructure with ultrafine equiaxed grains and approximately 75 % high-angle grain boundaries, facilitated by extensive dynamic recrystallization. In contrast, the Ni interlayer led to the formation of brittle Al-Ni-Fe compounds with approximately 74 % low-angle grain boundaries, whereas the Zr interlayer resulted in Al₁₃Fe₃Zr₈ intermetallics and a mixed microstructure. Transmission electron microscopy analysis confirmed the presence of a crystalline nanofibrous AlFeTi₂ network in the Ti joints, which enhanced load transfer and crack resistance. These results highlight the importance of interlayer selection for optimizing the interfacial microstructures and enhancing the performance of dissimilar Al-steel FSW joints.